Comparative study of antibiotic resistance in bacteria isolated from dog and chicken - Victor, Atere; Samuel, Alo; Folashade, Daniel (International Journal of Scientific World, 2017)
The emergence of antibiotic resistance has caused a threat to both human and animal population. This research was designed to investigate and compare the antibiotic resistance of bacteria isolated from chicken and dogs. A hundred and twelve samples of freshly dead chicken and eighty nine blood samples of sick dogs were analyzed. Pure culture of isolates were identified using cultural, morphological and biochemical characteristic. In vitro, susceptibility of the identified isolates against antimicrobial agents were determined by the standard disk diffusion procedure. One hundred and six isolates were recovered from chicken while 27 isolates were recovered from dogs. The organisms isolated include E. coli, Haemophilus sp, Pasturella sp, Klebsiella sp, Enterobacter sp, Salmonella sp, Staphylococcus sp., Micrococcus sp., Pseudomonas sp, Proteus sp, and Listeria sp. The antibiotic resistance showed that, gram-negative bacteria showed more resistance to the antibiotics used in this research compare to the gram-positive bacteria. This trend was found in isolates from both dog and chicken. In like manner, the bacteria isolates recovered from chicken showed a greater resistance when compare with the bacteria isolates recovered from dog. The increased resistance found in poultry makes poultry a suspect of residual resistance gene and probably reservoir for transmission.